Leaflet anatomy of zamia disodon d.w. stev. and amp; sabato and z. restrepoi (d.w. stev.) a. lindstr. (2013)
The genus Zamia is morphologically and ecologically the most diverse of theCycadales. Colombia is the country where most living species of Zamia have beenrecorded. Even though in the past this genus extended beyond the Neotropical region,nowadays it is almost entirely restricted to that biogeographical realm. As with theremaining Cycadales, this genus shows several unusual anatomical traits in theleaflets. The objective of this research was to study and compare the leaflet anatomyof Zamia disodon and Z. restrepoi and establish possible relationships between theanatomical traits and the habitats of these species. We found that both species shareseveral unusual traits with each other and with other species of the genus, such asthe parenchyma morphology, the distribution of tissues between the veins and thestomata morphology. The main differences between these species were seen in theirfiber clusters and in the distribution and abundance of the photosynthetic tissue nearthe vein areas. The presence of stomata both adaxially and abaxially could be theresult of the very wet habitats where both species are native, while the presenceof fiber clusters just at the vein areas could account for the longevity of the leavesof Zamia. On the other hand the unique traits of Zamia restrepoi are related to thepresence of a midvein, a trait not found in any other species of Zamia.